2022
DOI: 10.1039/d2qo01403c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the synthetic application of sulfinyl radicals

Abstract: Sulfinyl radicals are typical sulfur-centered π-radicals that have been known since 1957, but their utilization in synthetic chemistry has so far been limited. The majority of significant progress in this...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…The radical sulfinylation reaction is much less developed compared with radical sulfonylation, perhaps due to the lack of sufinyl-inducing reagents . Sulfinyl sulfones are known to react with nucleophiles, and more recently, Bi and Larionov showed that alkyl radicals engage in radical sulfinylation with this type of reagent . They can be readily prepared by the reaction of sulfinates with an acylating reagent.…”
mentioning
confidence: 99%
“…The radical sulfinylation reaction is much less developed compared with radical sulfonylation, perhaps due to the lack of sufinyl-inducing reagents . Sulfinyl sulfones are known to react with nucleophiles, and more recently, Bi and Larionov showed that alkyl radicals engage in radical sulfinylation with this type of reagent . They can be readily prepared by the reaction of sulfinates with an acylating reagent.…”
mentioning
confidence: 99%
“…Based on the observations and previous publications, ,,, a proposed mechanism for the transformation is depicted in Scheme . It begins with an electron transfer from photoexcited 4CzIPN to NHPI ester.…”
Section: Resultsmentioning
confidence: 92%
“…Compared with disulfenylation, thiosulfonylation and disulfonylation, the sulfinysulfonylation of unsaturated bonds is less investigated. The utilization of sulfinyl radicals 145 in synthetic chemistry is relatively limited compared with the well-established sulfonyl and thiyl radical-participated reactions. This might be attributed to the inherent characteristics of sulfinyl radicals, which tend to undergo homodimerization to form thiosulfonates, or engage in reversible additions to π-systems via β-elimination of the sulfinyl group (Scheme 116).…”
Section: Sulfinylsulfonylationmentioning
confidence: 99%